A positive electrode material and its preparation method and application
By using compound a, conductive agent and adhesive with a quinone structure in the lithium-ion battery positive electrode material, a positive electrode material with high specific capacity and good cycle stability was prepared, which solved the problem of poor electrochemical performance of the existing positive electrode material and achieved more efficient battery performance.
Patent Information
- Application Number
- CN202211141543.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-09-19
AI Technical Summary
The electrochemical performance of existing lithium-ion battery cathode materials is not good enough and is not renewable, which has adverse effects on the environment.
A positive electrode material including compound a, conductive agent and binder is adopted. Compound a has a quinone structure and is prepared by vacuum drying and grinding, so as to ensure that the mass percentage of compound a in the positive electrode material is less than or equal to 80%.
The high specific capacity and good cycle stability of lithium batteries are achieved, and the charging and discharging specific capacity of the first round can reach 132mAh/g, which has good application prospects.
Smart Images

Figure QLYQS_1 
Figure HDA0003852262760000011 
Figure HDA0003852262760000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to positive electrode materials, and in particular to a positive electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of the electric new energy vehicle industry and large-scale renewable energy, people's demand for batteries with high energy density, long cycle life, high reliability and stability is increasing day by day.
[0003] Among several common types of rechargeable batteries, lithium-ion (LIBs) batteries have become the mainstream direction of current rechargeable batteries because of their high energy density and excellent cycle performance. They also have the advantages of light weight, long cycle life, high energy density, small memory effect, and environmental friendliness. The composition of the positive electrode material in lithium batteries determines the electrochemical performance and production cost of the battery. At present, the positive electrode materials in the field of lithium batteries are mainly inorganic metal oxides, such as LiCoO2, LiMn2O4 and LiFePO4, but they are metal materials and are non-renewable, which makes them unfavorable for the sustainable development of the industry and does not conform to the concept of green environmental protection. In recent years, organic electrode materials have become ideal positive electrode materials with great potential because they have the following advantages: 1) Organic materials are composed of organic elements (such as C, H, O) that are abundant in the earth's crust, and have the potential for low cost and harmlessness to the environment. 2) Organic materials have the characteristics of light weight, flexibility, good mechanical properties, and good safety performance. 3) The molecular structure of organic materials can be flexibly adjusted to meet different electrochemical performance requirements. Based on the above advantages, various organic materials are considered to be the future development trend of positive electrode materials for lithium-ion batteries. However, the electrochemical performance of positive electrode materials prepared from existing organic electrode materials is still not good enough.
[0004] Based on this, there is an urgent need for a more stable battery positive electrode material with better performance. Summary of the invention
[0005] The first technical problem to be solved by the present invention is:
[0006] A positive electrode material is provided.
[0007] The second technical problem to be solved by the present invention is:
[0008] A method for preparing the positive electrode material is provided.
[0009] The third technical problem to be solved by the present invention is:
[0010] Application of the positive electrode material.
[0011] In order to solve the first technical problem, the technical solution adopted by the present invention is:
[0012] A positive electrode material, comprising the following components:
[0013] Compound a, a conductive agent and a binder;
[0014] The mass percentage of the compound a in the positive electrode material is less than or equal to 80%;
[0015] The structural formula of the compound a is as follows:
[0016] .
[0017] According to the embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects:
[0018] 1. Compound a containing a quinone structure is beneficial to improving the stability of the positive electrode material.
[0019] 2. The greater the mass percentage of compound a in the positive electrode material, the higher the utilization rate of compound a (active material), and when the positive electrode material is loaded on the battery, the greater the capacity of the battery. However, compound a is an organic material, and organic materials often have the problem of high solubility, and high solubility often leads to poor cycle performance. Therefore, compound a needs to be in a balanced state in the positive electrode material. Based on this, the mass percentage of compound a in the positive electrode material is less than or equal to 80%.
[0020] 3. The positive electrode material prepared by the present invention can achieve a first-cycle charge and discharge specific capacity of 132 mAh / g in a lithium battery assembly test, has a high specific capacity and good cycle stability, and has good application prospects in the field of lithium battery positive electrode materials.
[0021] According to one embodiment of the present invention, the mass ratio of the compound a, the conductive agent and the adhesive is 2-8:2-8:1, preferably 2-3:6-8:1.
[0022] According to one embodiment of the present invention, the mass percentage of the compound a in the positive electrode material is 30%-60%.
[0023] According to one embodiment of the present invention, the mass percentage of the compound a in the positive electrode material is 40%-60%.
[0024] According to one embodiment of the present invention, the mass percentage of the compound a in the positive electrode material is 50%-60%.
[0025] According to one embodiment of the present invention, the mass percentage of the compound a in the positive electrode material is 60%-70%.
[0026] According to one embodiment of the present invention, the mass percentage of the compound a in the positive electrode material is 70%-80%.
[0027] According to one embodiment of the present invention, the conductive agent includes at least one of conductive carbon black, acetylene black, graphene and carbon nanotubes.
[0028] According to one embodiment of the present invention, the binder includes at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, hydroxypropyl methyl cellulose, polyvinyl alcohol and polyimide.
[0029] In order to solve the second technical problem, the technical solution adopted by the present invention is:
[0030] A method for preparing the positive electrode material comprises the following steps:
[0031] The compound a, the conductive agent and the binder are mixed and vacuum dried to obtain the positive electrode material.
[0032] According to one embodiment of the present invention, the method further comprises a grinding step.
[0033] According to one embodiment of the present invention, the vacuum drying temperature is 80°C.
[0034] According to one embodiment of the present invention, the vacuum drying time is 8 hours.
[0035] Another aspect of the present invention also relates to the application of the positive electrode material in a lithium battery, including the positive electrode material as described in the first embodiment. Since the application adopts all the technical solutions of the positive electrode material of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.
[0036] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0038] Figure 1 This is the infrared spectrum of the positive electrode material prepared in Example 1.
[0039] Figure 2 This is a charge and discharge curve test diagram of the lithium battery prepared in Example 1.
[0040] Figure 3This is a test diagram of the charge and discharge cycle curve of the lithium battery prepared in Example 1. DETAILED DESCRIPTION
[0041] Embodiments of the present invention are described in detail below, examples of the above embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0042] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0043] In the description of the present invention, it should be understood that descriptions involving orientation, such as orientation or positional relationship indicated as up, down, etc., are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0044] In the description of the present invention, it should be noted that, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention in combination with the specific content of the technical solution.
[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0046] Example 1
[0047] A method for preparing a positive electrode material, the specific steps are as follows:
[0048] Add 3 mg of compound a, 6 mg of multi-walled carbon nanotubes and 1 mg of polyvinylidene fluoride into a graphite mortar. Grind and stir for 20 minutes to fully mix the three materials. Put the evenly mixed powder into a tablet press and press it into tablets by applying pressure to obtain a finished pole piece. Put the finished pole piece into a vacuum oven and dry it at 80°C for 8 hours. Take the positive pole piece of Example 1 to prepare a lithium battery. The specific preparation process is as follows:
[0049] In an argon glove box, the positive electrode and glass fiber diaphragm are assembled in sequence, the electrolyte is added, and then the lithium sheet and gasket spring are placed. After pressure packaging, the preparation of the lithium battery is completed.
[0050] Among them, compound a was purchased from McLean with the product number P832644-5g. The structural formula of compound a is as follows:
[0051] .
[0052] Example 2
[0053] A method for preparing a positive electrode material, the specific steps are as follows:
[0054] 1) Add 6 mg of compound a, 3 mg of multi-walled carbon nanotubes and 1 mg of polyvinylidene fluoride into a graphite mortar.
[0055] 2) Grind and stir for 20 minutes to fully mix the three materials.
[0056] 3) Put the evenly mixed powder into a tablet press and press it into tablets by applying pressure to obtain finished pole pieces.
[0057] 4) Place the finished electrode in a vacuum oven for drying, set the temperature to 80°C, and dry for 8 hours.
[0058] Take the positive electrode sheet of Example 2 to prepare a lithium battery. The specific preparation process is as follows:
[0059] In an argon glove box, the positive electrode sheet of compound a and the glass fiber diaphragm are assembled in sequence, the electrolyte is added, and then the lithium sheet and the gasket spring are placed. After pressure packaging, the preparation of the lithium battery is completed.
[0060] Among them, compound a was purchased from McLean with the product number P832644-5g. The structural formula of compound a is as follows:
[0061] .
[0062] Example 3
[0063] A method for preparing a positive electrode material, the specific steps are as follows:
[0064] 1) Add 4 mg of compound a, 5 mg of multi-walled carbon nanotubes and 1 mg of polyvinylidene fluoride into a graphite mortar.
[0065] 2) Grind and stir for 20 minutes to fully mix the three materials.
[0066] 3) Put the evenly mixed powder into a tablet press and press it into tablets by applying pressure to obtain finished pole pieces.
[0067] 4) Place the finished electrode in a vacuum oven for drying, set the temperature to 80°C, and dry for 8 hours.
[0068] Take the positive electrode sheet of Example 3 to prepare a lithium battery. The specific preparation process is as follows:
[0069] In an argon glove box, the positive electrode sheet of compound a and the glass fiber diaphragm are assembled in sequence, the electrolyte is added, and then the lithium sheet and the gasket spring are placed. After pressure packaging, the preparation of the lithium battery is completed.
[0070] Among them, compound a was purchased from McLean with the product number P832644-5g. The structural formula of compound a is as follows:
[0071] .
[0072] Example 4
[0073] The difference between Example 4 and Example 1 is that the structural formula of compound a is different.
[0074] A method for preparing a positive electrode material, the specific steps are as follows:
[0075] Add 3 mg of compound a, 6 mg of multi-walled carbon nanotubes and 1 mg of polyvinylidene fluoride into a graphite mortar. Grind and stir for 20 minutes to fully mix the three materials. Put the evenly mixed powder into a tablet press and press it into tablets by applying pressure to obtain a finished pole piece. Put the finished pole piece into a vacuum oven and dry it at 80°C for 8 hours. Take the positive pole piece of Example 4 and prepare a lithium battery. The specific preparation process is as follows:
[0076] In an argon glove box, the positive electrode and glass fiber diaphragm are assembled in sequence, the electrolyte is added, and then the lithium sheet and gasket spring are placed. After pressure packaging, the preparation of the lithium battery is completed.
[0077] Among them, compound a was purchased from McLean with the product number P832644-5g. The structural formula of compound a is as follows:
[0078] .
[0079] Example 5
[0080] The difference between Example 5 and Example 1 is that the structural formula of compound a is different.
[0081] A method for preparing a positive electrode material, the specific steps are as follows:
[0082] Add 3 mg of compound a, 6 mg of multi-walled carbon nanotubes and 1 mg of polyvinylidene fluoride into a graphite mortar. Grind and stir for 20 minutes to fully mix the three materials. Put the evenly mixed powder into a tablet press and press it into tablets by applying pressure to obtain a finished pole piece. Put the finished pole piece into a vacuum oven and dry it at 80°C for 8 hours. Take the positive pole piece of Example 5 to prepare a lithium battery. The specific preparation process is as follows:
[0083] In an argon glove box, the positive electrode and glass fiber diaphragm are assembled in sequence, the electrolyte is added, and then the lithium sheet and gasket spring are placed. After pressure packaging, the preparation of the lithium battery is completed.
[0084] Among them, compound a was purchased from McLean with the product number P832644-5g. The structural formula of compound a is as follows:
[0085] .
[0086] Performance Test:
[0087] Take the positive electrode of Example 1 and perform infrared spectrum test. The test results are as follows: Figure 1 As shown by Figure 1 It can be seen that compound a was successfully loaded onto the positive electrode.
[0088] Take the lithium battery prepared in Example 1, and perform a lithium battery charge and discharge curve test in a blue battery test system to obtain a voltage-specific capacity curve of the battery, such as Figure 2 As shown in the figure, it can be seen that the first cycle charge and discharge specific capacity of the lithium battery based on the positive electrode material of the present invention can reach 132 mAh / g at a current of 50 mA / g.
[0089] Take the lithium battery prepared in Example 1 and perform a lithium battery charge and discharge cycle curve test in a blue battery test system. Figure 3 As shown, it still shows good cycle performance after 100 cycles, which shows that it has good application prospects in the field of lithium battery positive electrode materials.
[0090] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: Includes the following components: Compound a, a conductive agent and a binder; The mass percentage of the compound a in the positive electrode material is less than or equal to 80%; The structural formula of the compound a is as follows: 。 2. A positive electrode material according to claim 1, characterized in that: The mass ratio of the compound a, the conductive agent and the adhesive is 2-8:2-8:
1.
3. A positive electrode material according to claim 1, characterized in that: The mass percentage of the compound a in the positive electrode material is 30%-60%.
4. A positive electrode material according to claim 1, characterized in that: The conductive agent includes at least one of conductive carbon black, acetylene black, graphene and carbon nanotubes.
5. A positive electrode material according to claim 1, characterized in that: The binder includes at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, hydroxypropyl methyl cellulose, polyvinyl alcohol and polyimide.
6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The compound a, the conductive agent and the binder are mixed and vacuum dried to obtain the positive electrode material.
7. The method according to claim 6, characterized in that: Also included is a grinding step.
8. The method according to claim 6, characterized in that: The vacuum drying temperature is 80°C.
9. The method according to claim 6, characterized in that: The vacuum drying time is 8 hours.
10. Use of a positive electrode material according to any one of claims 1 to 5 in a lithium battery.